Mutating RBF Can Enhance Its Pro-Apoptotic Activity and Uncovers a New Role in Tissue Homeostasis. - Milet, C.; Rincheval-Arnold, A.; Moriéras, A.; Clavier, A.; Garrigue, A.; Mignotte, B.; Guénal, I. (PLoS ONE, 2014)
The tumor suppressor retinoblastoma protein (pRb) is inactivated in a wide variety of cancers. While its role during cell cycle is well characterized, little is known about its properties on apoptosis regulation and apoptosis-induced cell responses. pRb shorter forms that can modulate pRB apoptotic properties, resulting from cleavages at caspase specific sites are observed in several cellular contexts. A bioinformatics analysis showed that a putative caspase cleavage site (TELD) is found in the Drosophila homologue of pRb (RBF) at a position similar to the site generating the p76Rb form in mammals. Thus, we generated a punctual mutant form of RBF in which the aspartate of the TELD site is replaced by an alanine. This mutant form, RBFD253A, conserved the JNK-dependent pro-apoptotic properties of RBF but gained the ability of inducing overgrowth phenotypes in adult wings. We show that this overgrowth is a consequence of an abnormal proliferation in wing imaginal discs, which depends on the JNK pathway activation but not on wingless (wg) ectopic expression. These results show for the first time that the TELD site of RBF could be important to control the function of RBF in tissue homeostasis in vivo.